Evaluating Digital Rehabilitation Outcomes in Chronic Musculoskeletal Conditions Across Non-Obesity, Obesity, and Severe Obesity [Letter] - Zeng X (Journal of Pain Research)
Xuefan Zeng Chongqing Medical University, Chongqing, 400016, People’s Republic of ChinaCorrespondence: Xuefan Zeng, Chongqing Medical University, No. 21, Mid University Town Road, Chongqing, 400016, People’s Republic of China, Email zxfcqmu@163.com